KEKERASAN TERHADAP PEREMPUAN DALAM CERPEN “PENGUBURAN KEMBALI SITARESMI”, “JEMARI KIRI”, DAN “LETEH”: KAJIAN INTERSEKSIONALITAS - Ekasiswanto, Rudi (Paradigma: Jurnal Kajian Budaya, 2025)
This research discusses the typology of violence in the short stories “Penguburan Kembali Sitaresmi”, “Jemari Nayla”, and “Leteh” by using Johan Galtung’s concept. The analysis also employs an intersectional approach to reveal the social categories that enable violence and to compare the violence across the three short stories. This research shows several findings. Firstly, in the first short story, direct violence (murder) and structural violence (marginalization) occur. In the second story, there is direct violence (sexual harassment) and structural violence (marginalization). In the third story, structural violence (stigmatization) is prevalent. Secondly, all three stories depict violence against women, but they also exhibit distinct patterns. Similarities and differences are based on criteria such as the victims, perpetrators, forms, and causes of violence, as seen in Table 2. Thirdly, the research finds that these short stories emerged during a time when past violations of women's rights remained unresolved and the state failed to take responsibility, while simultaneously, violence against women continued to escalate.